New data on the treatment of kala-azar (Mediterranean visceral leishmaniasis) - Giraud, Paul; Bernard, Rene; Orsini, A.; Coignet, J. (The Turkish Journal of Pediatrics, 1962)
The authors wish to call attention to the fact that in recent medical publications severe and many times fatal accidents during treatment of visceral leishmaniasis in both children and adults are reported.They emphasize the fact that their opinion is based upon their experience since 1922 when they first started their study of the disease and their actual clinical experience since 1944 when they began their work with the actual techniques of treatment. They feel that kala - azar is a disease that can be cured in a period of two to three months with proper treatment.To prevent severe complications, the utmost caution must be used in the administration of treatment.Kala - azar, a disease which undetected and untreated causes almost certain death, can, in the present day, be cured within a reasonable period of time.